Coronary Microvascular Function and Beyond: The Crosstalk between Hormones, Cytokines, and Neurotransmitters - Carlo Dal Lin; Francesco Tona; Elena Osto (International Journal of Endocrinology)
Beyond its hemodynamic function, the heart also acts as a neuroendocrine and immunoregulatory organ. A dynamic communication between the heart and other organs takes place constantly to maintain cardiovascular homeostasis. The current understanding highlights the importance of the endocrine, immune, and nervous factors to fine-tune the crosstalk of the cardiovascular system with the entire body. Once disrupted, this complex interorgan communication may promote the onset and the progression of cardiovascular diseases. Thus, expanding our knowledge on how these factors influence the cardiovascular system can lead to novel therapeutic strategies to improve patient care. In the present paper, we review novel concepts on the role of endocrine, immune, and nervous factors in the modulation of microvascular coronary function.